(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
This article details why we learn and teach foreign language. The basic goal of learning a foreign language is to acquire the communicative competence, while the development and improvement of such competence is to some extent dependent of efficient and scientific teaching approach